Clinico-Pathological Profile of Cutaneous Lupus Erythematosus Patients: A Report from A Tertiary Care Center of Chattogram - Mowla, Mohammad Rafiqul; Barua, Deva Pratim; Zaman, Shakila; Hossain Chowdhury, Mohammad Ismail; Dutta, Papri; Ali Mridha, Md Wazed (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2021)
Background : Nearly all epidemiologic studies have involved patients with Systemic Lupus Erythematosus (SLE). Few authors have investigated the characteristics of patients with Cutaneous Lupus Erythematosus (CLE). We aim to describe the epidemiologic, clinical, and immunologic characteristics of a series of patients diagnosed with CLE. Materials and methods : This is a descriptive retrospective cross-sectional study carried out using the register records of total 218 patients attending the ‘Lupus Clinic’ in Chittagong Medical College Hospital during the period 2010 and 2020. The disease activity and damage of CLE were assessed according to the Cutaneous Lupus Erythematosus Disease Area and Severity Index (CLASI). Results : There were 187 females (86%) and 31 males (14%) with the female: male ratio being 6.1:1. The mean age was 28 ± 10.06 (mean ± SD) ranging between 11 and 65 years. The Chronic Cutaneous Lupus Erythematosus (CCLE) patients accounted 154 (71%) followed by Acute Cutaneous Lupus Erythematosus (ACLE) 46 (21%) and Subacute Cutaneous Lupus Erythematosus (SCLE) 18 (8%). On the basis of CLASI score, 91 (42%) patients were in mild form, 85 (39%) in moderate form and 42 (19%) in severe state. In LE specific skin lesions, common manifestation was photosensitivity 198 (91%) followed by discoid rash 154 (71%) and maculo-papular lupus rash 55 (25%). Oral ulcer was seen in 49 (22%) patients and malar rash in 46 (21%) patients. Other observed LE specific skin manifestations were papulo squamous rash 11 (5%), Toxic epidermal necrolysis like lesions 7 (3%) and lichenoid lesions 6 (3%). Among LE nonspecific skin lesions, common manifestation was nonscarring alopecia 123 (56%) followed by Raynaud’s phenomenon 17 (8%) livedo reticularis 17 (8%) Vasculitis 15 (7%) Periungual telangiectasia 7 (3%) erythema multiforme 6 (3%) and leg Ulcer 5 (2%). Antinuclear Antibody (ANA) 132 (61%) was the most common autoantibody followed by anti-ds DNA 91 (42%) anti-Sm antibody 2 (1%) anti-phospholipid antibodies 9 (4%) and anti-RNP 3 (1%). Hematological manifestations were seen in 161 (73.85%) where erythrocyte sedimentation rate was the most common hematological abnormality 161(73.85%) followed by lymphopenia 126 (57.80%) leucopenia 113 (51.80%) thrombocytopenia 107 (49.10%) anemia 92 (42%) monocytopenia 37 (16.97%). Conclusions: CCLE was the most common subtypes of CLE. Patients with different subtypes of CLE have distinct clinical and pathological characteristics. The onset or concurrence of SLE mandates the involvement of other disciplines depending on organ involvement. In the absence of consensus on a definition that makes it possible to differentiate cutaneous forms of LE from SLE, the dermatologist’s role in the correct diagnosis and classification of such patients is fundamental. Chatt Maa Shi Hosp Med Coll J; Vol.20 (2); July 2021; Page 79-84